Towards Green ELT: An Education for Sustainable Development-Driven Analysis of Environmental Behavior, Technology Integration, and Language Competence - Ridha Deprianita; Anita Triastuti; Rizky Amelia; Murodjon Atakuziev (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2026)
This study investigates how environmental science integration, value, pro-environmental behavior, and technology integration contribute to English language competence. The researchers used PLS-SEM with 5,000 bootstrap resamples for the data analysis of 624 senior high school students in South Kalimantan through a questionnaire containing 21 items. The measurement model showed satisfactory reliability and validity, while the structural model revealed some significant relationships. The findings demonstrated that ESI significantly enhances TI (β = 0.258, p < 0.001), and VPB also significantly enhances TI (β = 0.383, p < 0.001). This supports that environmental interaction and values are important drivers for the willingness of students to use digital technology in learning. At the same time, TI significantly predicts LC (β = 0.440, p < 0.001), showing that technology is a pathway to improving language competence within an ESD-oriented framework. These findings have implications for theorizing the integration of ESD and technology-enhanced language learning by showing how environmental engagement and digital practices intersect in support of language development. The study also has practical implications for teachers and policymakers in incorporating environmental themes and digital tools in the teaching of English in order to simultaneously foster sustainability awareness and strengthen language competence.